Correction: Syntheses, X-ray structures, gas adsorption and luminescent properties of three coordination polymers of Zn(ii) dicarboxylates mixed with a linear, neutral, and rigid N, N′-donor ligand. Issue 9 (7th March 2015) - Bhattacharya, Biswajit; Maity, Dilip Kumar; Dey, Rajdip; Ghoshal, Debajyoti
<x xml:space="preserve">Abstract</x> Correction for 'Syntheses, X-ray structures, gas adsorption and luminescent properties of three coordination polymers of Zn(ii) dicarboxylates mixed with a linear, neutral, and rigid N, N′-donor ligand' by Biswajit Bhattacharya et al., CrystEngComm, 2014, 16, 4783–4795.